2016
DOI: 10.3402/ecrj.v3.31601
|View full text |Cite
|
Sign up to set email alerts
|

Availability of pulmonary rehabilitation in primary care for patients with COPD: a cross-sectional study in Sweden

Abstract: BackgroundPulmonary rehabilitation (PR) is an important, evidence-based component for the management of individuals with chronic obstructive pulmonary disease (COPD). In daily practice, the majority of COPD patients are treated in primary care. However, information about the availability of PR in primary care in Sweden is lacking. The aim was to investigate the availability of rehabilitation resources in primary care settings for patients with COPD in Sweden.MethodsA cross-sectional descriptive design was appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Our previous study [15] and a recent systematic review [37] showed that healthcare professionals sometimes felt they themselves lack competence in supporting self-management, or they considered self-management to be outside their daily practice, and therefore they chose to refer patients to others for support. The access to pulmonary rehabilitation in Swedish primary care is rather low [15,43], and the organization (management in primary care) must provide opportunity for its healthcare professionals to feel competent enough and have time to educate and support empowerment among people with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [15] and a recent systematic review [37] showed that healthcare professionals sometimes felt they themselves lack competence in supporting self-management, or they considered self-management to be outside their daily practice, and therefore they chose to refer patients to others for support. The access to pulmonary rehabilitation in Swedish primary care is rather low [15,43], and the organization (management in primary care) must provide opportunity for its healthcare professionals to feel competent enough and have time to educate and support empowerment among people with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also indicate that telemonitoring may have a potential role as a valuable complement to existing health care. It is known that patients with COPD do not receive the recommended health care [ 39 , 52 ]. Considering this, it would be unethical not to further explore eHealth solutions, such as telemonitoring, since it can contribute to more equity in health care.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that GPs did not refer patients to PR as often as they should have. This is particularly noteworthy given the accessibility of PR in Swedish primary care [ 25 ]. Previous researchers found that GPs’ inadequate knowledge of the role of PR in treatment, insufficient experience, and lack of routines explained their low rates of referral to PR [ 26 ].…”
Section: Discussionmentioning
confidence: 99%